2016
DOI: 10.1016/j.childyouth.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Behavior problems and children's academic achievement: A test of growth-curve models with gender and racial differences

Abstract: The aim of this study was to examine the longitudinal association between externalizing and internalizing behavior and children’s academic achievement, particularly in terms of whether these variables varied as a function of gender and race. Data pertaining to externalizing and internalizing behavior, academic achievement, gender, and race from three waves of the Child Development Supplement of the Panel Study of Income Dynamics (N = 2028) were used. Results indicate that behavior problems had a negative relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 53 publications
(72 reference statements)
4
65
0
Order By: Relevance
“…Fourth, the findings of this study indicate that children's problem behavior influences their academic performance. Such results are similar to the findings of a longitudinal study conducted on children in the U.S. [23], which reported that children's problem behavior is related to academic performance. It M=mean, SD=standard deviation…”
Section: Discussionsupporting
confidence: 89%
“…Fourth, the findings of this study indicate that children's problem behavior influences their academic performance. Such results are similar to the findings of a longitudinal study conducted on children in the U.S. [23], which reported that children's problem behavior is related to academic performance. It M=mean, SD=standard deviation…”
Section: Discussionsupporting
confidence: 89%
“…The data analysis also revealed that parents' level of job qualifications is positively related to adolescent academic achievement, which in turn is negatively correlated with adolescents' problem behavior. A similar link between academic achievement and problem behavior has been identified in other studies (Kremer, Flower, Huang & Vaugh, 2016). It should be noted that the relationship between parental qualifications and academic achievement is statistically significant only as regards maternal qualifications, which may be explained by culturally defined gender roles.…”
Section: Discussionsupporting
confidence: 83%
“…School engagement has also emerged as protective against problem behaviors, such as internalizing and externalizing, for youth in the general population (Hirschfield & Gasper, 2011;Shochet, Dadds, Ham, & Montague, 2006). Internalizing and externalizing behaviors can impede academic achievement (Kremer, Flower, Huang, & Vaughn, 2016;Riglin, Petrides, Frederickson, & Rice, 2014) and are unfortunately prevalent among youth in foster care (e.g., Baker, Schneiderman, & Licandro, 2017). More research is needed to better understand associations between school engagement and behavior problems among foster youth, in order to effectively inform muchneeded intervention efforts.…”
mentioning
confidence: 99%